PKM Konseling Personal Hygiene pada Lansia di Wilayah Pesantren Nurul Jadid Karanganyar Paiton Probolinggo - Vivin Nur Hafifah; Shofiatul Widad; Nafilatin Mabruro; Nur Laila (GUYUB: Journal of Community Engagement, 2021)
Personal hygiene is an act to maintain the cleanliness and health of a person for physical and psychological well-being. Lack of knowledge and information about the importance of personal hygiene makes the elderly not think too much about the impact that personal hygiene will have on the elderly. So that education (counseling) related to personal hygiene can increase knowledge in the elderly about the importance of maintaining and caring for personal hygiene. This counseling uses audiovisual in the form of video media (AVA or Audio Visual Aids). The result of this community service is a fact that the counseling went well and the elderly felt happy with the knowledge that was given. A healthy and clean lifestyle needs to be continuously socialized because cleanliness is the root of health and the elderly are susceptible to various diseases that originate from body uncleanness.